Impact of airport operations and road traffic on the particle number concentration in the vicinity of a suburban airport - Fritz, Sabine; Grusdat , Felix; Sharkey , Rowan; Schneider , Christoph (Frontiers in Environmental Science, 2022)
The impact of airports on ambient air pollution is a major concern due to its impact on public health. This study analyzes the sub-micron total particle number concentration (PNC) as a proxy for ultrafine particles in the immediate vicinity of Berlin-Tegel Airport (TXL) based on a mobile measurement campaign in summer 2019. With predominantly westerly winds, 45 measurement runs took place along a 20–30 km route to the east of the airport. The highlights of the study are as follows: 1. Berlin-Tegel Airport had a distinct but a spatially limited impact on the residential areas to the east of the airport. 2. Particle number concentrations in the lee of the airport are significantly higher than the mean of the entire area. 3. Locations along the eastward extension of the runways are significantly more affected than those outside the approach corridor. 4. The impact of airport operations on PNC in the adjacent neighborhood is comparable to the combined impact of busy roads in the area. The closure of Berlin-Tegel Airport at the end of 2020 should have considerably improved the air quality in the residential areas in the close vicinity of the airport.